Proyecto de evaluación de procesamiento y comercialización de bebida refrescante orange aloe para la provincia de Santa Elena - Plúa Mera, Aura (2009)
In the present project a market research is carried out and financial feasibility for the implementation of a micro-business food processor and trader refreshing beverages Orange Aloe, which will include a technology based on the prosecution and processing of the sabil, orange and honey with commodity clearly would originate of the Peninsula of Santa Elena and adjoining zones in presentation of not returnable plastic container of 135ml, obtaining in this manner A completely natural product. The motivation of this study situates in which the implementation of this micro-business employed the natural properties of the sabil that combined with the orange and honey they offer its own benefits of beverages 100% without perseverates in order to offer to the consumer a novel, healthy product and above all guaranteed therefore complies with the norms required for elaboration of food. The study covers an analysis of financial viability to detail the costs that implies the creation and development of this micro-business, the incomes that is foreseen to obtain and of that form, with financial criteria and taking as base the market research, the convenience of the project